Impact of Exchange Rate Volatility on Growth and Economic Performance: A Case Study of Malaysia - Khang, Poh Tze (2009)
This paper will try to analyze the effect of exchange rate volatility on the growth and economic performance of Malaysia from year 1990 to year 2009. Malaysia has been through several exchange rate regimes during the period, from free floating exchange rate regime in the early 1990s to fixed exchange rate during the Asian Financial Crisis until 2005 and finally managed float exchange rate regime since then until now. Graphs showing the performance of several Malaysia’s economic indicator are provided. By performing Unit Root Test on Malaysia’s economic data such as Real Effective Exchange Rate, Imports and Exports, M2 money supply and Industrial Production Index and calculating the volatility of the Real Effective Exchange Rate, it is determined that the above mentioned data are of stationary at first difference. In addition, Granger causality test is performed to search for any cause and effect relationships between these variables. Results show that there is a one sided cause and effect relationship between Industrial Production Index and Real Effective Exchange Rate Volatility. In conclusion, there is no significant effect of exchange rate volatility on Malaysia’s economical performance.